Learning Taxonomy of Islamic Education: The Development of Aql and the Brain in Quran from a Neuroscience Perspective - Suyadi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
The hierarchical thinking concept in the Islamic education field is based on theological and philosophical beliefs. Up to now, this concept is not yet proven scientifically and neurobiologically. As a result, Islamic education does not yet have a learning taxonomy that accommodates the effective and spiritual aspects of developing students' intellectual potential. Consequently, it forced its system to apply Bloom’s taxonomy which focuses only on the cognitive part. With the rising of new theories, especially neuro-theology, neuro-philosophy, and neuro-education, emerge the opportunities to connect hierarchical thinking in Islamic education with these three theories. This research aims to compile a learning taxonomy of Islamic education based on neuroscience, accommodating the emotional, intellectual, and spiritual aspects. This research is a systematic review, which integrates, interprets, and synthesizes the hierarchical thinking concept with neuro-theology, neuro-philosophy, and neuro-education. The result shows that hierarchical thinking in Islamic education has neuro-physiological with six brain components: temporal lobe, parietal association cortex-temporal-occipital, limbic system, cingulate gyrus, prefrontal context, and prefrontal association cortex. These six components of the brain have relevance to hierarchical thinking and bloom taxonomy, namely remember (dzikir), understand (nazhr), apply (‘ilm-amal), evaluate (muhasabah); analyze (fikr), and create (ijtihad). Thus, the brain's six components and hierarchical thinking can be narratively synthesized into a learning taxonomy of Islamic education. In the future, this finding could become theoretical discourse because hierarchical thinking, neuro-theology, neuro-philosophy, and neuro-education emerge the further development of learning taxonomy in Islamic education.